A Comparative Study Of Student Perceptions On Vocabulary Learning Using Duolingo And Elsa - Vivi Ayu Lestari; Ahmad Najib Mutawally; Arif Budimansyah Purba; Wafiqah Yasmin; Anwar Hilman; Wahyudi Wahyudi; Ludovikus Ludovikus (Journal of Innovative and Creativity, 2025)
In the current asynchronous teaching at Horizon University Indonesia, students are still using several English learning applications and media, such as Duolingo, ELSA, and others. These tools are employed as a means of remote learning specifically aimed at supporting the Global Workplace English Program (GWEP) at Horizon University. The purpose of using these media is to help Horizon students improve their English test scores (EFSET) as part of their preparation for entering the workforce, as well as to enhance their four English language skills. Based on this, we are conducting a study to determine which application is most suitable and can encourage students at Horizon-U to be more active, and motivated, and ultimately improve their vocabulary in English. Vocabulary is one of the language aspects which should be learned. Learning vocabulary is important because people can speak, write, read and listen. Moreover, people have to know the vocabulary first. It means that in learning vocabulary, people need to know and understand the meaning of vocabulary and how to use vocabulary in the right context. In this research, the researcher used qualitative methods, including questionnaires and interviews, to gather information on students’ perceptions. This study was conducted in two classes at Horizon-U, with 50 participants from GWEP 4 providing positive feedback about the Duolingo and ELSA applications. Therefore, the researcher aims to explore the students’ perceptions of using Duolingo and ELSA, focusing on the topic “A Comparative Study of Student Perceptions on Vocabulary Learning Using Duolingo and ELSA.”